IMPROVING DIGITAL LEARNING: EVALUATING THE U LEARN LMS WITH THE SYSTEM USABILITY SCALE - Sudestra, I Made Ardi; Agustini, Ni Wayan Eva; Gunawan, I Made Agus Oka; Indrawan, Gede; Hakimi, Musawer (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2024)
The assessment of the usability of online learning systems is becoming more and more critical in order to ensure that users have the best possible experience. This study employed the System Usability Scale (SUS) to assess the usability of the learning management system at UNDIKNAS, using 68 students from various academic programs as participants. The employed methodology is administering a SUS questionnaire consisting of 10 items on a Likert scale from 1 to 5. The points are computed using the standard SUS methodology and multiplied by 2.5 to derive the final score. The analysis disclosed an average SUS score of 56.65, falling short of the academic usability benchmark 68. The score distribution visualization indicated that most respondents rated between 50 and 60, highlighting the need for system improvement. The SUS assessment of the learning management system at UNDIKNAS reveals that the system's usability necessitates improvement. Key recommendations include improving the user interface, optimizing navigation, and providing user guides to enhance the overall user experience